Implications of high commodity prices on poverty reduction in Ethiopia and policy options under an agriculture-led development strategy - Beyene, Lulit Mitik (International Food Policy Research Institute, 2014)
This research aims at measuring the potential impact of high commodity prices on Ethiopia’s prospects of maintaining agricultural growth objectives and poverty reduction targets set in the CAADP agenda. In view of this, we build a Computable General Equilibrium model which uses the Dorosh and Thurlow (2009) approach as a benchmark. We then introduce international oil and fertilizer price shocks along with a devaluation policy. A poverty analysis is conducted using the latest household income and consumption expenditure survey.